2022
DOI: 10.1186/s12877-022-03393-w
|View full text |Cite
|
Sign up to set email alerts
|

Complementary support in later life: investigating the gender disparities in patterns and determinants among older adults in South-Western Nigeria

Abstract: Old-age needs are multifaceted and require multiple support sources, yet caregiving roles for older Nigerians are largely shifted to adult children. However, the children also declining capacity to respond. The extent to which older adults access support from other sources remains under-researched. This study investigates the patterns and determinants of access to complementary supports among older adults in South-Western Nigeria, taking Oyo State as the case study. The study is cross-sectional and utilized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, this study finds that living in a household headed by someone else, especially by a family member, protects older persons from MD. Although being a household head could give older persons some authority over household members and resource allocation [ 32 ], this benefit is conditional on the availability of resources, the extent of affinity, sense of responsibility and reciprocity, and the functional ability of the household head. Thus, older persons living in households headed by a younger, economically active and financially buoyant family member are more likely to have access to information, communication and companionship, healthcare support and quality living standards, compared with those with otherwise living arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study finds that living in a household headed by someone else, especially by a family member, protects older persons from MD. Although being a household head could give older persons some authority over household members and resource allocation [ 32 ], this benefit is conditional on the availability of resources, the extent of affinity, sense of responsibility and reciprocity, and the functional ability of the household head. Thus, older persons living in households headed by a younger, economically active and financially buoyant family member are more likely to have access to information, communication and companionship, healthcare support and quality living standards, compared with those with otherwise living arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that children tend to provide more support to their mothers than to their fathers [ 51 , 52 ]. However, the higher unmet need among men may not be linked solely to limited family support but also to the preservation of self-independence and dignity among men in patriarchal societies [ 28 ]. In the modern African family setting, as shown in this study, support in old age is predominantly sourced from immediate family members, including children and spouse.…”
Section: Discussionmentioning
confidence: 99%
“…Financial limitations may also hinder their ability to afford the costs of travelling and providing medium- or long-term support [ 25 ], and the physical challenges faced by caregivers due to health issues can limit their capacity to provide support. While additional support may be offered by other available social networks, it may not be appropriate or adequate for ADL support [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ebimgbo, Atama, et al (2022) , the well-being of older individuals including the widowed should be the primary focus of several support systems to enable them to achieve healthy aging. In Nigeria, the roles of various support systems like family, community, and friends in the care of older adults have been established ( Ebimgbo, Agwu, et al, 2021 ; Ebimgbo, Atama, et al, 2022 ; Ebimgbo, Chukwu, et al, 2021 ; Ebimgbo, Nnama-Okechukwu, et al, 2022 ; Ebimgbo & Okoye, 2017 ; Mobolaji & Akinyemi, 2022 ). Other studies have also acknowledged the role of religious organizations in the care of older adults.…”
mentioning
confidence: 99%
“…Also, Ede et al (2023) revealed that religious and spiritual participants are useful to the psychological health and the general well-being of older people in Nigeria. Among the South-western Nigeria population, the study by Mobolaji and Akinyemi (2022) discovered the significant role of religious organizations in the support of older adults, whereas in Bauchi, North-Eastern Nigeria, Yakubu and Namadi (2018) found that older adults who are Moslems deeply practice the activities of Jeedo to enable them to age in place and to achieve life satisfaction. Among the widows, studies have documented the roles of church-based organizations in reducing their challenges through financial, material, and information support ( Agubuzu-Oyi, 2014 ; Zhiya, 2015 ).…”
mentioning
confidence: 99%